Disparities in material facilities in public elementary schools in the division of Sulu and their effects in pupil learning - De Leon, Florentina S. (1985)
This paper analyzed the morpho-phonemic changes that occur in the formation of Ilongo verbs. The data consisted of 300 words gathered from Visayan magazines and from conversations among native speakers of Ilongo. It was found that assimilation, consonant change, vowel change, loss or addition of phoneme, stress shift, metathesis, and reduplication occur in Ilongo verb formation. It is hoped that the study be a part of the basis for a comparative analysis between Ilongo and other Philippine languages.